Three-dimensional CAD/CAM imaging of the maxillary sinus in ageing process - Lovasova, Kvetuse; Kachlik, David; Rozpravkova, Mirela; Matusevska, Maria; Ferkova, Jana; Kluchova, Darina (Annals of anatomy, 2018)
OBJECTIVES: During the physiological ageing process atrophy of the alveolar bone appears in vertical direction. This bone resorption causes pushing the limits of the maxillary sinus at the expense of a degraded bone. The sinus volume increases due to the facial development in children and adolescents or during the ageing process due to the loss of teeth and bone mass. The main aim of this study is to determine the sinus shape and sinus floor morphology related to age. MATERIALS AND METHODS: Human adult male and female cadaveric heads (aged 37 to 83 years) with different dental status were used. The three-dimensional CAD/CAM software was used to scan the solid impressions of the maxillary sinus to visualize the real sinus shape and sinus floor. Subsequently, other findings are shown in tables and evaluated graphically. RESULTS: The maxillary sinus morphology, its relationship to the nasal cavity, the sub sinus alveolar bone height, displacement of the lowest and highest points of sinus, and the sinus relationship to the roots of the upper teeth were studied and evaluated. Some septa, crests, and the prominent infraorbital canal were also found in the area of the sinus floor. CONCLUSIONS: This paper provides a unique view on the maxillary sinus and its changes during the ageing process with preserved topographical relations in a representative sample of the Slovak population. The visualization of the maxillary sinus anatomy is necessary in the diagnosis and treatment plans for dental implants and during current surgical procedures.
Keywords: senioři; design s pomocí počítače; Aging; mrtvola; zuby; senioři nad 80 let; Cadaver; počítačové zpracování obrazu; Bone and Bones; Middle Aged; mužské pohlaví; Tooth; Adult; Computer-Aided Design; Ageing process; Morphology; Maxillary sinus; processus alveolaris; Aged, 80 and over; Slovakia; Nasal Cavity; stárnutí; kosti a kostní tkáň; Slovenská republika; ženské pohlaví; Maxillary Sinus; Humans; nosní dutina; zobrazování trojrozměrné; 3D imaging; 3D scanning; anatomické modely; lidé středního věku; sinus maxillaris; Alveolar Process; Imaging, Three-Dimensional; Models, Anatomic; Image Processing, Computer-Assisted; Alveolar recess; dospělí; Female; Aged; lidé; Male